Literature Review: Pengaruh Terapi Murottal Terhadap Kecemasan Pada Pasien Hemodialisa - Wachidah Yuniartika; Febina Sulistyo; Framesti Nurjanah (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Abstract Renal failure is a slow, progressive and irreversible worsening of kidney function that causes the inability of the kidneys to remove waste products and maintain fluid and electrolyte balance. One of the effects that can be caused is anxiety. Patients undergoing hemodialysis experience anxiety due to several factors, especially physical conditions that are starting to weaken. Therefore, patients need therapy to reduce anxiety to foster positive perceptions. Murottal therapy is a therapy by listening to the recitation of the holy verses of the Koran, thus making the patient more comfortable and calm. This study was conducted to determine the effectiveness of murotal therapy on anxiety in hemodialysis patients. The research methodology used is Literature Review. Literature in the form of International Journals and National Journals published from 2015 – 2022. The collection of literature uses the Google Scholar and Pubmed databases with the keywords: Chronic Kidney Failure, Hemodialysis, Anxiety, Murottal Therapy. The search results obtained 276 articles according to keywords. After being filtered through a prism using inclusion and exclusion criteria, 4 articles were obtained consisting of 3 National Journals and 1 International Journal reviewed. The results of the review show that murottal therapy can reduce anxiety levels in hemodialysis patients.